Synthetic Versatility of Lipases: Application for Si–O Bond Formation and Cleavage - Brondani, Patrícia Bulegon; Mittersteiner, Mateus; Voigt, Morgana Aline; Klinkowski, Bruna Heloisa; Riva Scharf, Dilamara; de Jesus, Paulo Cesar (Synthesis, 2019)
Several commercially available lipases were examined in a study on O–Si bond formation and cleavage applying silicon-based protecting groups and alcohols or the corresponding silyl ethers. With regard to deprotection, from silyl ether to the corresponding alcohol, only the solvent and the lipase were necessary. The influence of the protecting group, the lipase source, and the substituent was investigated to optimize the results. The TMS moiety could be removed in 24 hours of reaction at room temperature in aqueous systems (conv. up to 99%, depending on the substrate and lipase). The reverse reactions, that is, with the protection of the alcohols, were carried out in hexane using different silyl chlorides. The TMS, TES, and TBS moieties were successfully inserted in the primary and secondary alcohols without the need for dry conditions or an inert atmosphere, presenting conversions of up to 99%, depending on the substrate.
Keywords: biocatalysis; lipases; silyl ethers; alcohol protection; alcohol deprotection